Personality Development In William Shakespeare’s Play Macbeth: Psycoanalytic Perspective - Juniar Elfrida Sitohang; Ruthertati Sianturi; Devina Sianturi; Mutia Khairunnisa Siregar; Syamsul Bahri (Lembaga Pengembangan Kinerja Dosen, 2025)
Literary works, especially drama, often reflect the complexity of human psychology through character development and internal conflict. One of the most profound ways to explore this complexity is through psychoanalytic theory, which reveals how unconscious forces shape human behavior. The objective of this study is to analyze personality development in William Shakespeare’s drama Macbeth through the lens of Sigmund Freud’s psychoanalytic theory. This study employs descriptive qualitative method to explore the inner conflicts experienced by the main character, Macbeth, which are categorized into Freud’s structural personality model: the id, ego, and superego. The results of the data were found that the most dominant component was the id (50%), followed by the ego (30.56%) and the superego (19.44%). The dominance of the id appears in Macbeth's ambition and unconscious desires that lead him to commit murder and violence to gain power. The ego appears when Macbeth tries to think rationally and consider the consequences of his actions, especially when he hesitates or plans strategically before taking any steps. The superego is found in Macbeth’s feelings of guilt and remorse after killing King Duncan, which show his moral awareness and internal punishment. The psychological tension caused by the conflict among the three components of personality reflects Macbeth’s mental transformation from a noble man to a tyrant driven by fear, guilt, and obsession. The final conclusion is that the id is the most dominant factor influencing Macbeth’s downfall, as his uncontrolled desires overpower his rational mind and moral conscience, causing his psychological destruction. This study shows that psychoanalytic theory can be a powerful tool to uncover the internal struggles of literary characters and explain how hidden psychological forces shape their fate.